Decolorization, Degradation and Subsequent Toxicity Assessment of Reactive Red 35 by Enterococcus gallinarum - K. Soni, Rakesh; Bhatt, N.S.; Modi, H.A.; Acharya, P.B. (Current Biotechnology, 2016)
Background: The textile industry is one of the greatest generators of liquid effluent pollutants. Azo dyes are widely used (60-70%) in textile and becoming major source of environmental pollutants. Hence, in present study, an attempt is made, to study the role of microbial systems for bioremediation of a vinyl sulfone-based monoazo dye, Reactive Red 35 (RR35). Methods: RR35 dye degrading bacterium was isolated from the Common Effluent Treatment Plant and identified on the basis of a 16s rRNA sequence. The physicochemical parameters were optimized for maximum dye decolorization and degradation. Biodegradation of RR35 was confirmed by FTIR, HPTLC, and GC-MS analysis. Proficiency of the treatment was evaluated by performing cytogenotoxicity with Allium cepa and phytotoxicity with Triticum aestivum, Pennisetum glaucum, Phaseolus mungo and Vigna radiata. Results: The results revealed that isolated bacterium Enterococcus gallinarum can efficiently decolorize RR35 (300 mg l-1) with the rate of 76.81 mg l-1 h-1 at 40°C, pH 7 under static condition. Yeast extract was proved as an efficient substrate for decolorization of RR35. The isolate could efficiently decolorize RR35 at higher salinity (40 g l-1). E. gallinarum decolorized 1500 mg l-1 RR35 within 7 h during five repetitive spiking of RR35. After 96 ± 0.53% decolorization of RR35, 41 and 50% COD removal was observed under static and agitated condition, respectively; upon consequent incubation for 36 h. Induced activities of oxidoreductases proved their contribution in degradation of RR35. The proposed metabolic pathway for the degradation of RR35 is elucidated for the first time, which showed production of lower molecules weight compounds, 1-amino 3-(1- sulfonyl-2-sulfooxy ethane) benzene, and naphthalene 1, 7-diamine. Conclusion: E. gallinarum can degrade and detoxify RR35 dye very efficiently.
Keywords: degradation